Influence of interleukin-10 gene polymorphism on the course of cystic fibrosis in children - N.M. Drobova (Zaslavsky O.Yu., 2018)
Background. Cystic fibrosis (CF) features depend on a number of gene modifiers. Interleukin-10 (IL-10) gene is a one of these gene modifiers. The purpose was to improve medical care for patients with CF by clarifying the pathogenetic role of the IL-10 gene polymorphism in the disease course. Materials and methods. Forty-two children with CF were examined with standard methods during the remission period. Detection of the G1082A polymorphism of the IL-10 gene was carried out using real time polymerase chain reaction. DNA was isolated from buccal epithelium cells. Results. Patients with IL-10 gene mutation (G1082A) were characterized by the earlier manifestation of intestinal symptoms, later manifestation of pulmonary signs, more severe course of CF (bronchiectasis (72 %) and lung fibrosis (95.4 %), severe liver lesions (36.4 %), a decrease in forced expiratory volume in one second (70.0 (65.0; 72.0) %)), Pseudomonas aeruginosa predominance (59.1 %) among respiratory pathological microorganisms in the sputum, immune status changes (an increase of the circulating immune complexes (8.65 (7.6; 10.55) units) and a decrease of spontaneous index of activated neutrophils test (0.31 (0.24; 0.78) units)). Conclusions. CF phenotype associated with the G1082A polymorphism of the IL-10 gene was examined.